2011
DOI: 10.1128/iai.00177-11
|View full text |Cite
|
Sign up to set email alerts
|

CD1d-Independent Activation of Invariant Natural Killer T Cells by Staphylococcal Enterotoxin B through Major Histocompatibility Complex Class II/T Cell Receptor Interaction Results in Acute Lung Injury

Abstract: There are two important mechanisms of activation of invariant natural killer T cells (iNKT cells)These studies not only demonstrate that iNKT cells can be activated directly by a bacterial protein superantigen independent of CD1d but also indicate that in addition to the conventional T cells, iNKT cells play a critical role in SEB-mediated ALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Activation of iNKT cells by CD1d glycolipid presentation to TCRs has been shown to induce cytokines such as IFN-g and IL-4 (40). However, antigenindependent mechanisms have also been described that rapidly facilitate iNKT cell activation (41)(42)(43)(44)(45). In support of this, Nowak-Machen and colleagues showed that pulmonary iNKT cells secreted significant levels of IFN-g and IL-17 after exposure to hyperoxia (46).…”
Section: Original Articlementioning
confidence: 56%
“…Activation of iNKT cells by CD1d glycolipid presentation to TCRs has been shown to induce cytokines such as IFN-g and IL-4 (40). However, antigenindependent mechanisms have also been described that rapidly facilitate iNKT cell activation (41)(42)(43)(44)(45). In support of this, Nowak-Machen and colleagues showed that pulmonary iNKT cells secreted significant levels of IFN-g and IL-17 after exposure to hyperoxia (46).…”
Section: Original Articlementioning
confidence: 56%
“…Previously, a single dose of SEB (50 g) by intranasal delivery was found to induce cellular infiltration, increase cytokine production, and cause histopathological lesions and edema in C57BL/6 mice (4, 21,22), mimicking the symptoms of acute inflammatory lung injury in humans (23). In this study, we first sought to investigate the inflammatory effect of SEB exposure in the lungs.…”
Section: Resultsmentioning
confidence: 99%
“…SEB dissolved in sterile phosphate-buffered saline (PBS) (2 mg/ml) was administered by the intranasal (i.n.) route in a volume of 25 l for a dose of 50 g per mouse, as described previously (4,21,22). Mice were euthanized 48 h after SEB exposure.…”
Section: Methodsmentioning
confidence: 99%
“…SEB binds to the nonpolymorphic regions of MHC II on antigen presenting cells and the specific V␤ regions of the T-cell receptor (TCR) such as murine V␤8, thereby activating a large population (up to 30%) of T cells that proliferate rapidly and trigger cytokine storm (17). Recent studies from our laboratory demonstrated that THC can attenuate SEB-mediated inflammation and toxicity to the lungs (18 -20).…”
mentioning
confidence: 99%